Analysis of Figurative Language in Selena Gomez’s Album Rare - Putri Wirastuti, I Gusti Agung; Yuliastuti, Ni Putu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2024)
Analysis of the types and meanings of metaphorical language in Selena Gomez's song lyrics from the album Rare is the goal of this study. Figurative language, or the manner an author describes what will be delivered, is a style of language use in essays. The use of language in certain circumstances, by specific writers, and for specific subjects is discussed in style (linguistic style).(Putra & Puspitasari, 2020). The researcher analyzing five song lyrics on Selena's